Development and design of the effect of adding a heatsink as a coolant on improvement output power on solar panels - Jalil, Asri Muhammad; Away, Yuwaldi; Nasaruddin, Nasaruddin; Sara, Ira Devi; Jalil, Saifuddin Muhammad (Institute of Advanced Engineering and Science, 2024)
This study discusses the use of solar energy as a clean and widely available alternative. The performance of solar panels is influenced by various factors including solar radiation, module, temperature, and distribution of the sunlight spectrum. Temperature issues in solar panels can be addressed through passive cooling, such as installing a heatsink. A passive cooling system is implemented by installing a heatsink with four layers of fins on the body panel of the solar module. The advantage of passive cooling with constellations is that it does not require additional energy from outside, while a large number of fins can achieve the best passive cooling constellation. Each heatsink utilizes eight fins with a total of three heatsinks, manufactured from aluminum. Vector values of wind speed, humidity, and temperature are studied through direct measurements. A 100 W polycrystalline solar module at a standard temperature of 25 ℃ produces an open circuit voltage of 22 +V.